(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2025)
The aim of the study was to estimate the prevalence of depression, anxiety, and stress symptoms, as well as overall life satisfaction, among school-aged children and adolescents in Armenia during COVID-19-related quarantine and school closures. A cross-sectional survey was conducted among 395 children aged 6–17 years attending secondary schools in Yerevan from March to April 2023. The Armenian version of the depression, anxiety and stress scale-21 (DASS-21) was used to measure psychological distress. The Fear of COVID-19 Scale (FCV-19S) and the Spielberger-Hanin anxiety test were also employed. Statistical analysis was performed using SPSS version 23.0. Descriptive and inferential statistics (t-test, ANOVA, Nonparametric tests, and χ2 test) were applied. Most schoolchildren demonstrated moderate levels of personal (48.1%) and situational (49.6%) anxiety. Girls showed significantly higher levels of both personal and situational anxiety compared to boys (p < 0.05). Mean anxiety scores were also higher in girls. According to DASS-21, symptoms of depression, anxiety, and stress were found in 59.9%, 57.2%, and 70.4% of participants, respectively, with the highest scores among adolescents aged 15–17. Younger children (6–10 years) had the lowest levels of psychological distress. The FCV-19S scale showed no significant differences by age or gender and demonstrated good reliability in assessing fear of COVID-19. DASS-21 demonstrated perfect age-group concordance, good predictive validity, and excellent internal consistency. Further evaluations of DASS-21 in different age groups are needed to optimize the scale. The international DASS-21 questionnaire is a sensitive and valid test for assessing depression, anxiety, and stress after COVID in school-aged children in Armenia.